ITSBAT NIKAH UNTUK MELEGALISASI PERKAWINAN (STUDI PUTUSAN PA. STABAT NOMOR: 219/PDT.G/2011/PA.STB.) - YULI SUCHI WARINA (PREMISE LAW JURNAL, 2015)
Marriage is the rights of every human beings, protected by religion and state. Therefore every citizen must be submissive and obedient to the rules. Law No.1/1974 on marriage states that 1) a marriage is legal if implemented in accordance with the law of respective religion and belief, 2) each marriage is registered in accordance with the existing regulation of legislation. But, in fact, still many marriages are not registered at the Office of Religious Affairs (KUA) or the Office of Civil Registration as the institution of marriage registrar. The consequence is that many unregistered marriages have inflicted problems later, if a marriage cannot be proven by showing a marriage certificate, its itsbat can be filed to the Religious Court and Muslim community members should register every marriage done to obtain legal consequences. The Judges who examine the cases of marriage itsbat should not complicate the itsbat application. The government or judicial institution through the Supreme Court should socialize the Law on Marriage and all of the regulations related to a marriage. Keyword : Marriage Legalization, Legalizing, Decision